Verified Nuclear Warhead Dismantlement: An Analysis and Methodology for Facility Assessment. Issue 1 (2nd January 2021) - Axelsson, Anders; Schofield, Jennifer; Sunhede, Daniel; Thompson, Nicholas J.; Laurie, Ian; Wilhelmsen, Katarina; Carter, Benjamin
Abstract: Effective verification of nuclear warhead dismantlement is an endeavor for which a solution is widely sought, but also one which poses numerous challenges, such as protection of information and safety and security of warheads and components. Some or all of these challenges could be influenced by the nature of the hosting dismantlement facility. We have developed a systems engineering approach for use in assessing this aspect of the dismantlement verification problem. We have used the methodology to evaluate which of four broad classes of facilities would be most favorable for verified dismantlement of nuclear warheads: a nuclear warhead facility engaged in active stockpile work, a nuclear warhead facility not currently in use for active-stockpile work, a converted industrial facility, and a purpose-designed dedicated dismantlement facility. The analysis is based on the level of challenge involved in implementing verified dismantlement, with respect to five key areas: Verification, Confidentiality, Safety, Security, and Compatibility with the overall nuclear warhead reductions regime. Using our method we find the option of the existing nuclear warhead facility not currently in use for active-stockpile work to be most favorable. On initial consideration, a dedicated dismantlement facility turns out to be the least favorable. This outcome is related to Compatibility and depends on the importance of making a dedicated dismantlement facility available in the same time frame as an existing nuclear warhead facility. If this criterion is relaxed, the dedicated dismantlement facility instead becomes the most favorable option. Verification, Confidentiality and Security have less impact on the overall outcome.